Evidence Around the Impact of Pulmonary Rehabilitation and Exercise on Redox Status in COPD: A Systematic Review - Watson, Alastair; Wilkinson, Tom M. A.; Freeman, Anna (Frontiers in Sports and Active Living, 2021)
Introduction: Oxidative stress is increasingly recognized as a significant factor in the pathogenesis of chronic obstructive pulmonary disease (COPD). Pulmonary rehabilitation, a major component of which is prescribed exercise, is essential in COPD care. Regular exercise has been proposed to increase antioxidant defenses and overall enhance the ability of the body to counteract oxidative stress. However, the mechanisms through which it improves COPD outcomes remain unclear. Objectives: We aimed to appraise the current evidence around the impact of pulmonary rehabilitation on redox status, compared with other exercise interventions, to gain an understanding of optimal exercise interventions to modify this pathophysiological mechanism. Methods: We performed a systematic review through searching CENTRAL, MEDLINE, PubMed, Scopus, and Web of Science. Results were independently reviewed and relevant studies were selected by two independent assessors. Studies were assessed by two independent people using the modified RoB 2 tool and discrepancies were resolved through discussion. Results: We identified 1,710 records and 1,117 records after duplicate removal. Six studies were included in the final analysis. The evidence available was low quality and four studies had high risk of bias and two studies had unclear risk of bias. Studies were small (15–56 participants); only two included details of randomization and patient cohorts were of varying ages and poorly described. Differences in smoking status and previous exercise levels, which are known to impact redox status, were not well documented. Studies were not standardized and used different exercise doses and measured different outcomes. One study reported lower malondialdehyde levels, a marker of lipid peroxidation, after pulmonary rehabilitation, compared with control. However, one study saw no difference following whole-body vibration training and another study showed higher malondialdehyde levels following supervised modified arm swing exercise compared with control. Conclusion: Understanding the impact of exercise on oxidative stress in COPD could lead to tailored exercise programs and modification of pathological mechanisms. However, we identify a lack of high-quality evidence to determine this. Larger, standardized, and high quality randomized controlled trials (RCTs) are essential, which use carefully clinically characterized and controlled cohorts to determine the relative impact of different exercise interventions on redox status to guide COPD management. We propose an idealized RCT design, which could be used to try and meet this need.